PERILAKU MASYRAKAT TERHADAP PERMINTAAN CRYPTOCURRENCY DI BANDA ACEH - Muhammad Zul Mausir; Chenny Seftarita (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract                                                                  This study is aimed to analyze about how the citizen’s behavior toward the demand of cryptocurrency in Banda Aceh. This study uses random purposive sampling method in collecting the data where the data is obtained through the interview toward the citizen from the nine districts in Banda Aceh. The model analysis that used is the qualitative descriptive analysis by using the following technique tabulation; editing, interpretation, and concluding. Based on the analysis, this study concludes that most of the cryptocurrency user are male that has the range of age between 22 to 24 years old. They use this cryptocurrency in order to raise the profit possibility and make the easiest transactions. Keywords: Cryptocurrency, Bitcoin, digital money.